2018
DOI: 10.3892/etm.2018.6844
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous isolation of mesenchymal stem cells and endothelial progenitor cells derived from murine bone marrow

Abstract: Mesenchymal stem or stromal cells (MSCs) are identified as sources of pluripotent stem cells with varying degrees of plasticity. Endothelial progenitor cells (EPCs) originate from either bone marrow (BM) or peripheral blood and can mature into cells that line the lumen of blood vessels. MSC and EPC therapies exhibit promising results in a variety of diseases. The current study described the simultaneous isolation of EPCs and MSCs from murine BM using a straightforward approach. The method is based on differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
(54 reference statements)
1
11
0
Order By: Relevance
“…The morphology of rabbit EPCs and BEPCs cultured for less than 2-3 weeks were stable during the culture with spindle-shaped appearance (Figure 1) that agreed with the previous studies [41,42,44]. The same shape of the early EPCs morphology originated from peripheral blood and/or bone marrow was observed for human [54], mouse [30], rat [31][32][33]35], goat [38] or chicken [39]. However, it has been demonstrated that longer culture (more than 3 weeks) of rabbit EPCs caused a change of morphology to cobblestone-like cells, although not in BEPCs culture [42,43].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The morphology of rabbit EPCs and BEPCs cultured for less than 2-3 weeks were stable during the culture with spindle-shaped appearance (Figure 1) that agreed with the previous studies [41,42,44]. The same shape of the early EPCs morphology originated from peripheral blood and/or bone marrow was observed for human [54], mouse [30], rat [31][32][33]35], goat [38] or chicken [39]. However, it has been demonstrated that longer culture (more than 3 weeks) of rabbit EPCs caused a change of morphology to cobblestone-like cells, although not in BEPCs culture [42,43].…”
Section: Discussionsupporting
confidence: 88%
“…However, it has been demonstrated that longer culture (more than 3 weeks) of rabbit EPCs caused a change of morphology to cobblestone-like cells, although not in BEPCs culture [42,43]. Similar morphological changes referred to the late EPCs were noticed in human, dog, sheep or goat EPCs from peripheral blood [22,[36][37][38]54], but even in the bone marrow-derived EPCs of mouse [30] and rat [31,33]. By contrast, chicken EPCs from bone marrow displayed a cobblestone pattern only after the induction with vascular growth endothelial factor [39], whereas goat bone marrow-derived EPCs did not change the spindle-shaped morphology over the longer culture [38].…”
Section: Discussionmentioning
confidence: 81%
“…It has been well characterized that infusion of EPCs either isolated from the bone marrow or by ex vivo cultivation could augment capillary density and neovascularization of ischemic tissue 14 . According to previous reports, EPCs obtained by our procedure share the same characteristics with early outgrowth EPCs, including surface markers CD 133 11 , and possess the ability to migrate, proliferate, differentiate into endothelial cells, form tube-like structure in vitro 11,14,15 , and promote angiogenesis in vivo 16 . It has been shown that the proper amount of EPCs' transplantation to promote angiogenesis in a rat model should be around 2 Â 10 5 to 2 Â 10 6 , without obstruction of coronary microcirculation 4,[17][18][19][20] .…”
Section: Discussionmentioning
confidence: 58%
“…EPCs are a heterogeneous group of endothelial cell precursors comprised of both hematopoietic and non-hematopoietic lineages derived from bone marrow and peripheral blood sources, respectively. Unlike traditional progenitor cells lacking self-renewal capacity, EPCs are similar to stem cells in their ability to self-renew, form clones, and differentiate into endothelial cells [104][105][106]. Their role in vasculogenesis-previously thought to occur only via migration of existing endothelial cells or through induction of hematopoietic stem cells-has been wellestablished [107].…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%